Wirtschaftspolitik der Deutschen Besetzungsbehörde im Bezirk Kolomyia (gemäss Zeitung "Volya Pokuttya” 1941 – 1944) - Aftanas, A. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2021)
Es werden die wichtigsten Aspekte der Wirtschaftspolitik der deutschen Verwaltung
im Bezirk Kolomyia von 1941 bis 1944 betrachtet. Behandelt werden
die Mobilisierungs- und Organisationsmaßnahmen der Behörden, um die Bevölkerung
zu finden und zur Arbeit ins Reich zu entsenden, sowie ihre Lebensumstände
und ihre soziale und rechtliche Stellung zu beschreiben. Die Rolle
der landwirtschaftlichen und handwerklichen Kurse, die im Bezirk Kolomyia
betrieben werden, wird separat analysiert. Es wurde festgestellt, dass die Organisation
der Berufsbildung den pragmatischen Überlegungen der NS-Verwaltung
entsprach, da militärische Misserfolge an der Front die Behörden dazu
veranlassten, die lokale Bevölkerung in das aktive Wirtschaftsleben einzubeziehen.
In der vorgeschlagenen Studie wird erstmals versucht, die Wirtschaftspolitik
des deutschen Besatzungsregimes in diesen Bereichen umfassend zu bewerten.
Daher sind die Ergebnisse dieser Untersuchung sowohl für die Weiterentwicklung
des historischen Regionalismus als auch im Kontext der Studien zum Zweiten
Weltkrieg von Bedeutung. This article examines the main aspects of the economic policy of the German
administration within the Kolomyia region during 1941–1944. On the bases of
„Vollia Pokuttya“ news, the directions of Germany economic governance in the
agrarian and trade commercial sector were singled out. The economic policy
pursued by the German occupation authorities in the Kolomyia region vividly reflected
the general trend of expansionist use of industrial and human potential
in the district of Galicia. This led to acts of disobedience and sabotage of grain
supplies by the peasants and a harsh reaction from the authorities. Nazi officials
pursued a similar policy in the cities. By allowing the resumption of business and
cooperatives, the Germans hoped to gain the loyalty of local residents. However,
support could not be achieved, as de facto control over the above institutions
continued to be exercised by various governmental economic groups, which
included all existing industrial organizations, craft associations, and consumer
cooperatives. Mobilization and organization government measures concerning
the departure of the population for job to the Reich were illuminated, and also
described their life conditions and social-legal status. In particular, the goal of
agricultural and handicraft courses, which operated in Kolomyia’s county, was
analyzed. The paper highlights that the organization of professional education
was suitable for pragmatic considerations of the Nazi administration, as military
failures give the power a push to attract local population to spend active agricultural
life.
This study is the first attempt of complex assessment of economic policy of
the German occupation regime in the mentioned terrains. Therefore, the results
of this paper are important both for the further development of historical regionalism
and in the context of studies devoted to the Second World War. Розглянуто головні аспекти економічної політики німецької адміністрації
у межах Коломийського округу протягом 1941–1944 рр. На основі дописів
газети «Воля Покуття» виокремлено напрями німецького господарського
урядування в аграрному та промислово-торгівельному секторах. Висвітлено
мобілізаційні й організаційні заходи влади щодо пошуку й відправки населення
на роботу в Райх, а також охарактеризовано його умови проживання й соціально-правовий статус. Окреслено становище й діяльність кооперативного руху в Коломийському окрузі. Окремо проаналізовано роль сільськогосподарських і ремісничих курсів, які діяли в Коломийському окрузі. Встановлено, що
організація фахової освіти відповідала прагматичним міркуванням нацистської адміністрації, оскільки воєнні невдачі на фронті стимулювали владу залучати місцеве населення до активного господарського життя.
У пропонованому дослідженні вперше здійснено спробу комплексної
оцінки економічної політики німецького окупаційного режиму на зазначених
теренах. Відтак результати цієї розвідки важливі як для подальшого розвитку історичної регіоналістики, так і в контексті студій, присвячених Другій світовій війні.